Recent Progress on Metal‐Based Nanomaterials: Fabrications, Optical Properties, and Applications in Ultrafast Photonics. (20th September 2021) - Fu, Bo; Sun, Jingxuan; Cheng, Yuan; Ouyang, Hao; Compagnini, Giuseppe; Yin, Peng; Wei, Songrui; Li, Shaojuan; Li, Dabing; Scardaci, Vittorio; Zhang, Han
Abstract: Nanomaterials have demonstrated excellent mechanical, thermal, optical, and electrical properties in various fields, including 1D carbon nanotubes, as well as 2D materials starting from graphene. Metal‐based nanomaterials, mainly divided into metal and metal oxide nanoparticles, also gradually come into the sight of ultrafast photonics applications due to the outstanding optical properties. The optical properties of metal nanoparticles can be enhanced by the interaction between conduction electrons with electric fields that is called surface plasmon resonance. As for metal oxide nanoparticles, optical properties are closely related to bandgap structures. When it comes to transition metal oxides, other phenomena also play important roles in optical absorption such as spin inversion and excitons of iron. Moreover, preparation methods of materials are also crucial for their properties and further applications. Therefore, in this review, commonly used physical and chemical fabrication methods for metal‐based nanomaterials are first introduced. Then the optical properties of typical metal and metal oxide nanoparticles are discussed specifically. In addition, the applications of metal‐based nanomaterials in ultrafast lasers based on mode‐locked and Q‐switched techniques are also summarized. Finally, a summary and outlook toward the synthesis, optical properties, and applications in ultrafast photonics of metal‐based nanomaterials are presented. Abstract : Metal‐based nanomaterials have gradually come into focus in the context of ultrafast photonics due to their outstanding optical properties. The state of the art of metal‐based nano materials in fabrications, optical pro perties, and applications as saturable absorbers are summarized in this review, aiming to accelerate the exploration of nanomaterials and further stimulate the applications in various fields.